The determinants of intellectual capital disclosure: a meta-analysis review - Houssem Eddine, Chaabane Oussama; Abdullah, Shamsul Nahar; Abdul Hamid, Fatima; Hossain, Dewan Mahboob (Emerald, 2015)
Purpose – The study aims to examine the relationship between the corporate disclosure on intellectual capital and five firm characteristics, namely, size, leverage, profitability, age and industry type. Design/methodology/approach – The research uses a meta-analysis technique by taking 19 articles published between 2003 and 2013. Thus, this study integrates and accumulates the findings of prior studies. Findings – The research finds a significant relationship between intellectual capital disclosure (ICD) and the independent variables: size, profitability and industry. Originality/value – This study provides a systematic overview of the determinants of ICD by using a meta-analysis approach. A systematic analysis is currently lacking in the ICD literature; hence, this study attempts to resolve the mixed findings of prior studies.